Coral Reef Condition in the Utilization Zone of Menjangan Kecil Island Karimunjawa Islands - Septya Anggoro Putri; Muhammad Zainudin; Riyanti Riyanti (Universitas Diponegoro, 2026)
Karimunjawa Islands is a national park that has abundant natural resource potential and high biodiversity, especially in coral reef ecosystems. However, the utilization of coral reef ecosystems for marine tourism development has a negative impact on the condition of coral reefs. This study aims to determine the physical and chemical conditions of waters, the growth forms of coral reefs, and the condition of coral reefs in the marine tourism utilization zone of Menjangan Kecil Island, Karimunjawa Islands. A survey method was used for this research. Data were collected at four stations using the Underwater Photo Transect (UPT) method and analyzed using CPCe software. The results showed that the physical and chemical conditions of the water, including temperature, brightness, and pH, were still suitable to support the survival and growth of corals. There were 13 types of coral growth forms found, including Acropora Branching (ACB), Acropora Digitate (ACD), Acropora Encrusting (ACE), Acropora Submassive (ACS), Acropora Tabulate (ACT), Coral Branching (CB), Coral Encrusting (CE), Coral Foliose (CF), Coral Heliopora (CHL), Coral Massive (CM), Coral Millepora (CME), Coral Mushroom (CMR), and Coral Submassive (CS). The highest percentage of hard coral cover was found at station 2, with a value of 84.17%, and the lowest was found at station 3, with a value of 62.01%. Overall, the condition of coral reefs in the marine tourism utilization zone of Menjangan Kecil Island was in the high category.